2015
DOI: 10.1108/ijbm-12-2013-0148
|View full text |Cite
|
Sign up to set email alerts
|

Customer satisfaction and loyalty in the United Arab Emirates banking industry

Abstract: Purpose – The purpose of this paper is to identify the determinants of consumer loyalty in Islamic and conventional banks in the United Arab Emirates (UAE). The study has relevance and importance in a country with a dual banking system. Since the products and services offered by the banks are largely homogenous, customer loyalty is mostly associated with the quality of certain tangible and intangible dimensions of service. It is important for the banks to understand the factors that lead to hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
2
23

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(120 citation statements)
references
References 56 publications
3
92
2
23
Order By: Relevance
“…The six dimensions of PAKSERV model had 20 items and adapted from previous developed scale by (Raajpoot, 2004). Customer satisfaction consisted of 3 items adapted from Sayani (2015) . Lastly, 3 items of customer loyalty adopted from .…”
Section: Instrument Developmentmentioning
confidence: 99%
“…The six dimensions of PAKSERV model had 20 items and adapted from previous developed scale by (Raajpoot, 2004). Customer satisfaction consisted of 3 items adapted from Sayani (2015) . Lastly, 3 items of customer loyalty adopted from .…”
Section: Instrument Developmentmentioning
confidence: 99%
“…According to a wide definitions, the generally accepted definition of customer satisfaction is a psychological state that results from consumer experiences after consumption (Rasheed & Abadi, 2014). Whether customer satisfied only depends on a product or service meets or exceeds customers' prior expectations (Sayani, H., 2015). Pi and Huang (2011), in their study on passengers in CKS International Airport in Taiwan, have found that satisfaction has a positive and significant influence on customer loyalty.…”
Section: Customer Loyaltymentioning
confidence: 99%
“…The three dimensions of SERVQUAL model had 9 items and adapted from previous developed scale by Parasuraman et al [37]. The subjective norm consisted of 3 items adopted from previous study by Fauziah et al Customer satisfaction consisted of 3 items adapted from Sayani [38]. Lastly, 3 items of customer loyalty adopted from Rahi et al [39].…”
Section: Instrument Developmentmentioning
confidence: 99%